(untitled) (Salud, Arte y Cuidado, 2021)
Study framed in the feasible project research modality, of descriptive character, supported by a field design, with a quantitative approach, its objective is to promote the existence of a Mothers´ Milk Bank in the Neonatal Pathology Unit of the Dr. Antonio Maria Pineda University Hospital, it was applied previously validated an instrument to 7 nurses from the aforementioned unit. In the results, it is highlighted that 100% of health staff considers necessary the creation of the Mothers´ Milk Bank, in the same way that 100% of the participants opine that the Breast Milk Bank would be beneficial for patients. Finally, 42% of the approached population considers that they have little knowledge about the organization and functionality of the Mothers` Milk Bank. In conclusion, the Bank in the Neonatal Pathology Unit represents a need and a beneficial idea for the patients of said unit. Likewise, it is concluded that the lack of knowledge about the Milk Bank by the Nursing staff represents a determining factor for its creation. All these assertions allowed determining the necessary tools to achieve the existence of the Breast Milk Bank in the Unit, beginning with the promotion through the execution of a protocol about the organization and functionality of the Milk Bank for nursing staff of the neonatal pathology unit, thus modifying one of the factors that condition the existence of the Mothers´ Milk Bank in this Unit.